Magic Marketing dalam Etika Bisnis Global: Kajian Literatur - Mansur; Gumiandari , Septi; Hamzawi , M. Adib (LP2M IAI Miftahul Ulum Pamekasan, 2023)
The inability of the businessman to compete sacrifices his ethics by involving shamanism and the magical world for income and money. By presenting a shamanic spell, it can realize business development. Business skills and experience seem to be able to overcome simultaneously with the magical world. The purpose of this research is to reveal the magical meaning in marketing. Secondary data was obtained from the qualitative data of 15 selected articles after being filtered from 147 data explored using Google Scholars through the Harzing's Publish or Perish (POP) application service which was published in the last 5 years. Search using the words